Good pharmacy practice standardized for community pharmacists: The lebanese order of pharmacists initiative - Souheil Hallit; Hala Sacre; Hilda Sarkis; Nadia Dalloul; Cynthia Abou Jaoude; Zeina Nahhas; Joya Dagher; Georges Sili; Pascale Salameh (Wolters Kluwer Medknow Publications, 2019)
Objective: The community pharmacist's role is in constant evolution. It shifted from compounding and dispensing to patient-centered services. To guarantee that all pharmacists are providing a service of appropriate quality to every patient, the Lebanese Order of Pharmacists (OPL) took the initiative of developing good pharmacy practice (GPP) guidelines to be applied by community pharmacists for services' quality improvement. Methods: Within the OPL, a Scientific Committee, the executive authority to organize scientific and educational activities, is appointed. It decided, in January 2018, to elaborate GPP guidelines for community pharmacists and created the Community Pharmacy Practice Subcommittee, which was in charge of this project. The GPP standards suggested by the OPL were inspired by the ones published by international organizations, namely the International Pharmaceutical Federation and WHO, American, European, and regional countries. Findings: The GPP standards comprised 15 sections that tackled the following topics: settings of a pharmacy, handling of stock, extemporaneous compounding, provision of medicines, supply of nonprescription medicines, interaction and communication, documentation systems, equipment, resources, health promotion, diagnostics, pharmacotherapy monitoring, research and professional development, trainees, and para-pharmaceuticals. Conclusion: The OPL was able to implement a first draft of the GPP standards for community pharmacists in Lebanon, a developing country with many constraints. The starting project will need to be consolidated by raising awareness and changing misconception among community pharmacists as a first step. Amendments to these guidelines will follow based on the pharmacists' feedback and results of an ongoing national survey conducted by the OPL and academia.